Original paperOptimizing parametrial aperture design utilizing HDR brachytherapy isodose distribution - Chapman, Katherine L.; Ohri, Nitin; Showalter, Timothy N.; Doyle, Laura A. (Journal of Contemporary Brachytherapy, 2013)
Treatment of cervical cancer includes combination of external beam radiation therapy (EBRT) and brachytherapy (BRT). Traditionally, coronal images displaying dose distribution from a ring and tandem (R&T) implant aid in construction of parametrial boost fields. This research aimed to evaluate a method of shaping parametrial fields utilizing contours created from the high-dose-rate (HDR) BRT dose distribution. Eleven patients receiving HDR-BRT via R&T were identified. The BRT and EBRT CT scans were sent to FocalSim (v4.62) ® and fused based on bony anatomy. The contour of the HDR isodose line was transferred to the EBRT scan. The EBRT scan was sent to CMS-XIO (v4.62) ® for planning. This process provides an automated, potentially more accurate method of matching the medial parametrial border to the HDR dose distribution. This allows for a 3D-view of dose from HDR-BRT for clinical decision-making, utilizes a paperless process and saves time over the traditional technique.